Investigation of corrosion, hardness, and wear rate of rice husk-zinc composite coating on A36 steel using dual anode electrolytic deposition technique - Samuel Ajayi; Peter Ikubanni; Peter Onu; Timothy A. Adekanye; Abideen T. Oyewo; Olufemi Ajide (Universitas Negeri Padang, 2025)
Zinc-bas ed composite coatings developed from synthetic ceramics (Si3N4, SiC, and Al2O3) have recently been employed as reinforcement to enhance their resistance to deterioration. However, there is limited literature on the utilization of ceramic particles sourced from agro-industrial wastes in the formulation of these coatings. This study investigated the effect of the surface improvement process (SIP) using rice husk (RH) nanoparticles on the hardness and wear rate of A36 steel. The A36 steel, zinc bar, and RH nanoparticles were procured and characterized using Energy Dispersive Spectroscopy (EDS). Four cathode specimens were produced, including an as-received specimen of A36 steel and two anodes of zinc. Four steel specimens coated with Zn-10RH(t25), Zn-10RH(t30), Zn-15RH(t25), and Zn-15RH(t30), denoted as S1, S2, S3, and S4, respectively, were developed with concentrations of 10 or 15 g/L and deposition times of 25 or 30 minutes at a constant cell voltage of 0.5 V. The as-received substrate steel was used as the control specimen (CS). The hardness and wear rate (WR) properties of the deposited samples were examined using Vickers hardness (HV) and a Pin-on-disc tribometer, respectively. All coated specimens exhibited substantial improvements in hardness and wear rate properties compared to CS (Hardness = 85.82±0.45 HV and WR = 2.45±0.34 g/min). For the coated specimens, the hardness and WR values ranged from 188.50 to 288.37 HV, 260.34 to 284.38 MPa, and 0.01 to 0.02 g/min, respectively. The inclusion of the coatings significantly enhanced the mechanical properties of the deposited specimens.